2002
DOI: 10.1097/00007890-200210150-00001
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 system in organ transplantation1

Abstract: The heme oxygenase-1 (HO-1) system, the rate-limiting step in the conversion of heme, is among the most critical of cytoprotective mechanisms activated during cellular stress. The cytoprotection may result from the elimination of heme and the function of HO-1 downstream mediators, that is, biliverdin, carbon monoxide, and free iron. HO-1 overexpression exerts beneficial effects in a number of transplantation models, including antigen-independent ischemia/reperfusion injury, acute and chronic allograft rejectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
142
1
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(151 citation statements)
references
References 61 publications
5
142
1
3
Order By: Relevance
“…We demonstrated that overexpression of HO-1 in renal tubular cells, either through gene transfer or induction with hemin, can protect these cells against cold storage injury (64). Our in vitro finding corroborates in vivo findings of others in heart, kidney, and liver transplantation models (30). HO-1 through the release of free iron stimulates synthesis of ferritin, the main cellular repository for free iron (64).…”
Section: Inducing Ho-1 Before Cold Storage: Another Strategy For Clinsupporting
confidence: 91%
See 1 more Smart Citation
“…We demonstrated that overexpression of HO-1 in renal tubular cells, either through gene transfer or induction with hemin, can protect these cells against cold storage injury (64). Our in vitro finding corroborates in vivo findings of others in heart, kidney, and liver transplantation models (30). HO-1 through the release of free iron stimulates synthesis of ferritin, the main cellular repository for free iron (64).…”
Section: Inducing Ho-1 Before Cold Storage: Another Strategy For Clinsupporting
confidence: 91%
“…The finding that iron is released in copious amount in the cold (26) and that HO-1, which induces ferritin, protects cells against cold strongly suggests ferritin as an important mechanism for HO-1 protection. HO-1 also produces CO and bilirubin, both of which are suggested to contribute to the cytoprotective properties of HO-1 (5,30). In essence, there is a strong scientific basis and much experimental backing to put the HO-1 concept to the test in a clinical trial.…”
Section: Inducing Ho-1 Before Cold Storage: Another Strategy For Clinmentioning
confidence: 99%
“…109 Evidence suggests that overexpression of heme oxygenase-1 (HO-1), also known as hsp32, exerts potent cytoprotective effects. 110,111 HO-1 belongs to a family of enzymes involved in the catabolism of heme into bilirubin, free iron, and carbon monoxide (CO) (Fig. 3).…”
Section: Experimental Strategies For the Manipulation Of Marginal Donorsmentioning
confidence: 99%
“…[110][111][112] HO-1 prevents the deleterious effects of heme, which promotes lipid peroxidation and free radical formation. 110 The mechanisms underlying HO-1's beneficial effects against IR injury have yet to be elucidated, but may be related to the production of CO. CO, released directly from heme, may act as a regulatory molecule in cellular and biologic processes, including endothelium vasodilatation, 113 inhibition of platelet aggregation, 114 suppression of inducible nitric oxide synthase, 112 down-regulation of procytokines via the mitogen-activated protein kinase pathways, 115 and inhibition of endothelial apoptosis. 116 Investigations in which HO-1 is up-regulated through pharmacologic induction (cobalt protophorphyrin) or gene therapy have shown promising results in attenuating IR injury and prolonging graft survival.…”
Section: Experimental Strategies For the Manipulation Of Marginal Donorsmentioning
confidence: 99%
“…HO-1 also possesses critical cytoprotective functions that are activated under cellular stress situations, such as inflammation, ischaemia, hypoxia, hyperoxia, hyperthermia or radiation [9]. HO-1 exerts major cytoprotective functions against inflammation, apoptosis and oxidative damage, and acts in the maintenance of microcirculation [10]. Accumulating evidence indicates that HO-1 plays an important role in immune regulation.…”
Section: Introductionmentioning
confidence: 99%